Features of the cytoprotection of gastric and duodenal mucosa in adolescents with chronic gastroduodenitis on the background of food hypersensitivity - V.S. Berezenko; M.S. Krotevich; T.A. Bogdanova; V.V. Zamula; H.E. Kozynkevych (Zaslavsky O.Yu., 2018)
Background. The cytoprotective properties of the gastrointestinal tract in children with chronic gastroduodenitis on the background of food hypersensitivity remain understudied. The purpose is to assess the state of the cytoprotective potential of gastric and duodenal mucosa in adolescents with chronic gastroduodenitis on the background of food hypersensitivity by determining the level of trefoil factor (TFF) 1 in gastric mucosa and TFF-2 - in gastric and duodenal mucosa by immunohistochemistry method. Materials and methods. Fifty adolescents (aged 12 to 17 years) were observed and divided into two groups. The first group consisted of 64 % (n = 32) of patients with chronic gastroduodenitis and food hypersensitivity; the second group included 36 % (n = 18) of children with chronic gastroduodenitis without food hypersensitivity. All children underwent morphological and immunohistochemical studies of biopsy specimens with the determination of TFF-1 and TFF-2. Evaluation of TFF-1 and TFF-2 expression was carried out on a point-scale according to the number of stained epithelial cells of the glands of the antrum and goblet cells in the field of view with a 40-fold magnification: 0 points - no color, 1 point - 30 % of stained cells, 2 points - 30-70 % of stained cells, 3 points - 70-100 % of stained cells. Results. A significant expression of TFF-1 (3 points) in the gastric mucosa occurred in adolescents of both groups. According to the results of the study, 62.5 % (n = 20) of children in the first group and 22 % (n = 4) of adolescents in the second group did not have staining of goblet cells (0 points) in duodenal mucosa, (c2 = 7.5; p = 0.008). Weak expression (1 point) occurred in 34.5 % (n = 11) of children in the first group and in the majority of children (67 % (n = 12)) in the second group (c2 = 4.84; p = 0.03). According to the results of statistical analysis, a group of children with food hypersensitivity has 17 times higher risk of atrophic changes in the duodenal mucosa. Conclusions. In children with food hypersensitivity, the cytoprotective properties of the duodenal mucosa are reduced, as evidenced by the absence of TFF-2 expression. In addition, microerosions, a decrease in the number of crypts and Brunner's glands in the duodenal mucosa are significantly more frequent in the group of children with food hypersensitivity in the absence or weak expression of TFF-2 (p < 0.05).